Processing of spatial sounds in human auditory cortex during visual, discrimination and 2-back tasks - Rinne, Teemu; Ala-Salomäki, Heidi; Stecker, G. Christopher; Pätynen, Jukka; Lokki, Tapio (Frontiers in Neuroscience, 2014)
Previous imaging studies on the brain mechanisms of spatial hearing have mainly focused on sounds varying in the horizontal plane. In this study, we compared activations in human auditory cortex (AC) and adjacent inferior parietal lobule (IPL) to sounds varying in horizontal location, distance, or space (i.e., different rooms). In order to investigate both stimulus-dependent and task-dependent activations, these sounds were presented during visual discrimination, auditory discrimination, and auditory 2-back memory tasks. Consistent with previous studies, activations in AC were modulated by the auditory tasks. During both auditory and visual tasks, activations in AC were stronger to sounds varying in horizontal location than along other feature dimensions. However, in IPL, this enhancement was detected only during auditory tasks. Based on these results, we argue that IPL is not primarily involved in stimulus-level spatial analysis but that it may represent such information for more general processing when relevant to an active auditory task.